Electromagnetic exposure levels of electric vehicle drive motors to cochlear implanted passenger - Xu-Wei Dong; Yi-Dan Qian; Mai Lu (PLoS ONE, 2025)
In order to evaluate the effects of electromagnetic radiation generated by the dual-drive motors of an electric vehicle on special passengers with cochlear implanted, this study considers a cochlear implanted passenger as the research object, takes the drive motors in electric vehicle as the exposure source. A calculation model including the vehicle body, brain tissue, skull, eyes, human body, and cochlear implant is built, and the finite element method is used to calculate the induced electric field (Ein), specific absorption rate (SAR), and temperature changes in different tissues and organs of the passenger’s body. The results show that the maximum value of Ein on the human body surface is 60.8 mV/m at the ankle. The Ein around the cochlear implant inside the human head is also high, with a maximum value of 57.1 mV/m. The maximum SAR of the human body is  1.99×10−6 W/kg, which also appears near the cochlear implant. Besides, the maximum temperature rise of the human body, brain tissue, and cochlear implant is 0.10 °C, 0.28 °C, and 0.0076 °C, respectively. Calculation shows that the Ein  and SAR of the human body and different tissues are much lower than the safety limit specified in the guidelines of the International Commission on Non-Ionizing Radiation Protection (ICNIRP), and the temperature rise does not reach the thermal damage threshold in the guidelines. The electric field around the electrode tip and the surface of the cochlear implant, the temperature rise of the cochlear implant also meet the requirements of the ICNIRP and the International Organization for Standardization’s 14708–7 medical device standard. The results could enrich the study on the electromagnetic environment of electric vehicles and provide references for the design and improvement of cochlear implants and electromagnetic exposure protection for vehicles.